EFEKTIVITAS PENGGUNAAN MEDIA INTERAKTIF WORDWALL DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS V SEKOLAH DASAR: Pendekatan Kualitatif - Icha Elisa Uli Kudadiri; Haryono; Sri Sumartiningsih; Agus Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of Wordwall learning media on students' learning interest. This study uses a qualitative descriptive research method with a literature study approach. Data collection techniques through observation, interviews, and documentation. The research participants were fifth grade students of SDN 101770 Tembung. The results of the study indicate that the use of Wordwall learning media has a positive effect on increasing students' learning interest, which is characterized by increased enthusiasm, attention, active involvement, and enjoyment of students in learning, increased understanding of concepts, ability to remember material, and achievement of better evaluation scores. The basic factors that affect children's low learning interest are boring teaching techniques, wordwalls can be used to assess knowledge. Fun and varied media will make students more motivated in following the learning process. This study contributes to the development of digital technology-based learning strategies at the elementary school level and provides practical implications for educators in optimizing the learning process.